IMPROVEMENT OF KNOWLEDGE RELATED TO FIRST AID IN BURN CONDITIONS - Dini Prastyo Wijayanti; Niken Ayu Sahella Putri; Mei Nur Faiz Nabillah; Fachrudin Albar; Annisa Fitriani; Nurul Komariyah; Asmaul Khusna (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2021)
Health promotion activities regarding the first treatment of burns at Senior High School of Islam, Sidoarjo is a form of community service in the form of counseling aimed at increasing children's knowledge about how to treat first burns which are an injury incident that occurs due to exposure to high temperatures. (complex soft tissue injury). The implementation of these activities on December 18, 2019 took place at Senior High School of Islam, Sidoarjo. With the target is students of Senior High School of Islam, Sidoarjo. Prior to the implementation of these activities, there was a process of preparing activities for approximately 2 weeks before the activities were carried out, starting from determining the theme of the extension to applying for permits to the parties concerned. As a form of evaluation, this activity was attended by 47 students of class X and XI, participants joined the activity happily and looked very enthusiastic, health promotion activities could run on time and smoothly.